Enhanced 2nd Order Gray Edge Color Constancy Algorithm Using Bilateral Filter (International Journal of Engineering and Computer Science, 2014)
The color constancy techniques becomes an important pre-processing technique which reduces the effect of the light source on the given image or scene. It is found that light effects lot on a given scene. So effect of the light source may degrades the performance of certain applications a lot like face recognition, object detection, lane detection etc. Color constancy has ability to detection of color independent of light source. It is a characteristic of the distinct color awareness organization which guarantees that the apparent color of objects remains relatively constant under altering illumination conditions. The overall goal of this paper is to propose a new algorithm 2nd order gray edge based color constancy algorithm using bilateral algorithm. The overall attention is to enhance the color constancy algorithm further. The histogram stretching is also used to improve the results. The comparison has shown the significant improvement over the available techniques.